COMPARATIVE STUDY ON THE EFFICIENCY OF DENTAL HYGIENE ACHIEVED BY MECHANICAL TECHNICS - Catalina Iulia Saveanu; Irina Bamboi; Raschip Laura; Carina Balcoș; Ana Nemțoi; Alexandra Ecaterina Saveanu; Octavian Boronia; Daniela Anistoroaei (Romanian Dental Association for Education, 2023)
Background: Individual dental hygiene is a fundamental component of plaque control, and toothbrushing is the main method for removing bacterial plaque. Incorrect manual brushing, excessive brushing, applying excessive force on the teeth, or even using incorrect techniques can cause gingival ulcerations in patients. Electric toothbrushes have significantly improved compliance. The aim of the study was to comparatively evaluate the efficiency of bacterial plaque removal from dental structures using mechanical means, specifically two electric toothbrushes: Oral-B Genius and Sonicare Diamond Clean. Materials and methods: The study included 20 subjects over the age of 20 from urban and rural areas who presented themselves at the Prevention Department of the University of Medicine and Pharmacy Iași for dental services. Data were recorded through a clinical examination performed by a single examiner who quantitatively and qualitatively evaluated the presence of bacterial plaque using the Quigley-Hein plaque index, the O'Leary index, and the Approximal Plaque Index (API). Results: The patient group consisted of 20 subjects, 13 females and 7 males, with an average age of 23.85 years, ranging from 20 to 29. 75% of the subjects were from urban areas, and 60% had a medium socioeconomic level. Conclusion Within the limits of this study, we can affirm that both methods effectively removed bacterial plaque, but the Philips Sonicare toothbrush demonstrated higher efficiency.